2018
DOI: 10.1016/j.bbadis.2018.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes – An autoinflammatory disease driven by metabolic stress

Abstract: Type 2 diabetes has traditionally been viewed as a metabolic disorder characterised by chronic high glucose levels, insulin resistance, and declining insulin secretion from the pancreas. Modern lifestyle, with abundant nutrient supply and reduced physical activity, has resulted in dramatic increases in the rates of obesity-associated disease conditions, including diabetes. The associated excess of nutrients induces a state of systemic low-grade chronic inflammation that results from production and secretion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 341 publications
2
48
0
Order By: Relevance
“…The latter contributes to a local pro‐inflammatory environment of adjacent cardiomyocytes with a substantial increase in macrophage infiltration . The development of inflammation in T2DM has been extensively reviewed, and here we focus on the key concepts of how a low‐grade systemic inflammation in T2DM affects mitochondrial metabolism.…”
Section: Pathophysiology Of Disturbances In Mitochondrial Metabolism mentioning
confidence: 99%
“…The latter contributes to a local pro‐inflammatory environment of adjacent cardiomyocytes with a substantial increase in macrophage infiltration . The development of inflammation in T2DM has been extensively reviewed, and here we focus on the key concepts of how a low‐grade systemic inflammation in T2DM affects mitochondrial metabolism.…”
Section: Pathophysiology Of Disturbances In Mitochondrial Metabolism mentioning
confidence: 99%
“…Increased blood glucose levels after food intake trigger pancreatic β‐cells in islets of Langerhans to secrete insulin, which stimulates glucose uptake by skeletal muscles and adipose tissues . Chronic low‐grade inflammation of islets in response to metabolic stress leads toward T2D . Abnormal increased levels of proinflammatory cytokines including Creactive protein (CRP), interleukin 6 (IL‐6), and IL‐1β are also observed in T2D patients that might activate innate immune response resulting in inflammatory mechanisms in pancreatic islets .…”
Section: Role Of Sfrp4 In Diabetes and Obesitymentioning
confidence: 99%
“…Abnormal increased levels of proinflammatory cytokines including Creactive protein (CRP), interleukin 6 (IL‐6), and IL‐1β are also observed in T2D patients that might activate innate immune response resulting in inflammatory mechanisms in pancreatic islets . Furthermore, different proinflammatory mediators including IL‐6, Tumornecrosis factor‐α (TNF‐α), IL‐1β, and IL‐1 dependent cytokines are released in islets of pancreas in response to hyperglycemia …”
Section: Role Of Sfrp4 In Diabetes and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple factors have been proposed to cause pathological changes in diabetes mellitus and its renal complications. Previous studies have shown that low-grade chronic inflammation and activation of the renin-angiotensin system (RAS) all accelerate the development of diabetes and its renal complications [4,5]. However, it is disappointing that the exact pathogenesis leading to T2DM and DKD remain not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%